Phase I clinical trial of NH130 and the prediction of its pharmacokinetics using physiologically based pharmacokinetic modeling - Kun Zhang; Shanshan Zhao; Jialin Du; Lan Zhang (Frontiers Media S.A., 2024)
BackgroundParkinson's disease psychosis (PDP) is a common and distressing complication of Parkinson's disease (PD), characterized by hallucinations and delusions. This research aimed to assess the pharmacokinetics and safety of NH130, a selective serotonin 5-HT2A inverse agonist, as a potential PDP treatment in healthy individuals.MethodsWe conducted clinical pharmacokinetic studies and safety evaluations for NH130, employing a physiologically based pharmacokinetic (PBPK) model to predict its behavior in human body.ResultsIn a single-dose escalation study, healthy volunteers received NH130 at varying doses (2 mg, 6 mg, 12 mg, 24 mg, 40 mg, 60 mg, and 90 mg) or a placebo. The drug demonstrated favorable pharmacokinetics, with no serious adverse events (AEs) reported. Clinical plasma concentrations correlated well with PBPK model predictions, validating the model's utility for guiding future clinical development.ConclusionNH130 showed promising pharmacokinetic characteristics and safety profile, supporting its progression to multi-dose trials and suggesting its potential as a therapeutic agent for PDP.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn/index.html, Identifier CTR20230409.